Evaluating the Implementation of Customer Service-specific Standard Operating Procedures in the Cashier and Operator Divisions - Utami, Bilqis Dwi; Widiyanti, Rikantini (Politeknik Negeri Bandung, 2024)
Dago Dreampark, a famous tourist destination in Bandung that has been operating for 7 years, has experienced positive or negative changes over time. These changes are evident in the decline and inconsistency of services in the past year, leading to complaints from tourists. To address this situation, a specific customer service SOP has been created for the cashier and operator divisions, which directly interact with customers. The Human Resources Department (HRD) plays a crucial role in addressing this issue through evaluation and training provided to employees in implementing the SOP. This study aims to evaluate the implementation of the new SOP at Dago Dreampark using a qualitative descriptive analysis method. The results of this research show significant positive impacts, with an average score of 4 on the questionnaire. Interviews with supporting staff and the General Manager reveal positive changes in appearance, handling of complaints, and improved service quality. Additionally, observations demonstrate positive changes in the implementation of SOP, communication with visitors, and coordination among employees. Despite encountering some obstacles, such as hairstyle discrepancies and the use of identification tags, it is expected that these issues can be resolved over time. This research provides an understanding of the success of the new SOP implementation at Dago Dreampark.